Repeated-root constacyclic codes of length 2ℓmpn - Chen, Bocong (2015)
For any different odd primes ℓ and p, structure of constacyclic codes of length 2ℓmpn over the finite field Fq of characteristic p and their duals is established in terms of their generator polynomials. Among other results, the characterization and enumeration of all linear complementary dual and self-dual constacyclic codes of length 2ℓmpn are obtained.